2013
DOI: 10.1017/s0305004113000558
|View full text |Cite
|
Sign up to set email alerts
|

Some reductions of the spectral set conjecture to integers

Abstract: The spectral set conjecture, also known as the Fuglede conjecture, asserts that every bounded spectral set is a tile and vice versa. While this conjecture remains open on ${\mathbb R}^1$, there are many results in the literature that discuss the relations among various forms of the Fuglede conjecture on ${\mathbb Z}_n$, ${\mathbb Z}$ and ${\mathbb R}^1$ and also the seemingly stronger universal tiling (spectrum) conjectures on the respective groups. In this paper, we clarify the equivalences between these stat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…Borrowing the notation from [5] and [21], we write S − T(G) (resp. T − S(G)), if the Spectral ⇒ T ile (resp.…”
Section: Fuglede and Pompeiu Problem 21 Fuglede's Spectral Set Conjementioning
confidence: 99%
“…Borrowing the notation from [5] and [21], we write S − T(G) (resp. T − S(G)), if the Spectral ⇒ T ile (resp.…”
Section: Fuglede and Pompeiu Problem 21 Fuglede's Spectral Set Conjementioning
confidence: 99%
“…In particular, the known fact that all tiling sets of a tile and all spectra of a spectral set are periodic offers some credibility to the conjecture [LW1,IK]. Moreover, some algebraic conditions, if satisfied, are sufficient to settle the conjecture on R, although these conditions are not easy to check [DL2].…”
Section: F (Q)mentioning
confidence: 99%
“…The case of finite cyclic groups is particularly interesting since Dutkay and Lai [3] showed that the tile-spectral direction of Fuglede's conjecture on R holds if and only if the discrete version holds for every finite cyclic group. They also showed that if the spectral-tile direction holds on R, then it holds for every finite abelian group.…”
Section: Introductionmentioning
confidence: 99%